The performance of Hungarian minority students in PISA assessments (2003–2022) - Papp Z., Attila (Central European Journal of Educational Research, 2025)
The analysis tries to describe the academic competencies of Hungarian minority students in the Carpathian Basin based on international PISA assessments. To this end, the author first addressed some methodological aspects of the PISA assessments and then presented some international data. Although the school competencies of Hungarian youth in Romania, Serbia, and Slovakia, as revealed by PISA data, show a fluctuating picture over time, a few patterns clearly emerge. First, one can see that while in Transylvania it appears that Hungarian students perform better than the majority students, in Slovakia the opposite is true, and in Vojvodina the homogeneity of the school-system is evident, as there is no significant difference here between Hungarian minority and majority youth. Despite the small sample sizes, one can still gain some insight into learning in a non-native language: in Romania and Serbia, this generally results in a disadvantage, but Slovakia stands out as an exception in this regard as well: here, it appears that choosing the majority language carries neither an advantage nor a disadvantage in terms of academic competencies. When interpreting academic performance, however, it is essential to take various background factors into account, primarily family background. The analysis highlights that the index of the socio-economic background of majority and minority Hungarian youth shows significant differences. To measure the net effect of the test language a linear regression model was elaborated. Using this, the author argues that the test language exerts a significant effect in the areas of mathematics and sciences.